Cross-domain secure data sharing using blockchain for industrial IoT - Singh, Parminder; Masud, Mehedi; Hossain, M. Shamim; Kaur, Avinash (Journal of parallel and distributed computing, 2021)
•A framework for cross-domain secure data sharing in the Industrial Internet of Things.•A system to manage false reporting and misbehaving using a penalty mechanism.•A framework for enhancing data integrity through multi-layer signatures. The Industrial Internet of Things (IIoT) enhances smart manufacturing process that escalates productivity through revolutionary techniques. The manufacturing process is sophisticated and complex because of various IoT domains (e.g. industries). A final product is an outcome of the efforts of several departments from different industries. However, this raises the cross-domain communication's privacy and security issues. Cross-domain data sharing for product manufacturing is a challenging research direction. This paper proposes a centralized cloud-based cross-domain data sharing platform using multiple security gateways. The security gateways use the blockchain to store the information into the centralized cloud. Once the application reported a malicious activity, the centralized cloud verifies the concern from the blockchain. Further, an action is taken against the party that performs malicious activity in the security gateways. The algorithms are designed for authentication and transaction of data. The proposed framework is able the secure data movement among different domains globally. The experiment result demonstrates that the proposed security and privacy framework helps to maintain trust among the industries that collaborate on manufacturing across the domains.